The Impact of Big Data on Purchasing and Procurement in Egypt - Sayed , Layla (Global Journal of Purchasing and Procurement Management, 2023)
Purpose: The study sought to analyze the impact of big data on purchasing and procurement in Egypt. Methodology: The research was conducted entirely on computers. Secondary data, or data that doesn't require actual observation in the field, are the focus of desk research. Because it requires little more than an executive's time, telephone rates, and directories, desk research is generally seen as a low-cost strategy in comparison to field research. As a result, the research used data that had already been collected and reported. This secondary data was readily available via the internet's digital library and scholarly articles. Findings: The results show that in conclusion, big data has had a significant impact on the way businesses operate, particularly when it comes to purchasing and procurement. It provides businesses with valuable insights into their customers' purchasing patterns and preferences. Big data is having a significant impact on purchasing and procurement in Egypt. It is enabling businesses, organizations and individuals to make more informed decisions, enhance efficiency and reduce costs Unique Contribution to Theory, Practice and Policy: Future research in the field of purchasing and procurement may be grounded in the behavioral theory and the resource dependency theory. Policymakers, researchers and academics from all across the world will all stand to gain from this study's findings. Executives in charge of national purchasing and procurement initiatives will also use the study's findings to boost the big data performance across the board. The research suggests that the purchasing and procurement sector should implement big data policies to boost the effectiveness of their primary operations and activities.